The internationalization of the state versus 'the causality of the international'. Issue 2 (12th April 2021) - Panitch, Leo; Gindin, Sam
Abstract: This article offers a critique of the attempt by Rosenberg and Boyle to use the theory of uneven and combined development not only to explain the Brexit referendum vote and Trump's presidential victory in 2016, but also to reinforce their case for recognizing 'the causality of the international' in the field of International Political Economy. The critique advanced here deploys a theorization of the internationalization of capitalist states under the aegis of an informal American empire, and points to the salience of state institutional capacities as well as changes in the balance of class forces inside China, the US and UK, to demonstrate that the argument forwarded by Rosenberg and Boyle is diminished by giving insufficient causal weight to class and state forces in the very constitution of the international in the era of global capitalism.